Evaluation of medication counseling practice at community pharmacies in Qassim region, Saudi Arabia - Abubakr A. Alfadl; Alian A. Alrasheedy; Musaad S. Alhassun (Elsevier, 2018)
Introduction: Pharmacists have a unique opportunity to promote good health through assuring the quality use of medicines. One of the most important tools to achieve this is medication counseling. Counseling plays an important role in enhancing medication adherence and optimizing medication therapy. Therefore, for improving the quality of services delivered by community pharmacists, it is essential to assess the current situation of counseling services delivered to patients. Aims and objectives: To date, there is a paucity of data regarding the quality of counseling services delivered to patients in community pharmacies in Saudi Arabia. This study aims to fill this gap through evaluating the counseling skills and counseling content delivered by pharmacists in a sample of community pharmacies in Qassim region, Saudi Arabia. Methods: The study was conducted at eleven community pharmacies in Qassim region. A convenient sample of community pharmacies was chosen based on their willingness to participate. To gather information, a form was prepared based on the core and complementary drug use indicators for evaluation of drug use in healthcare settings developed by the WHO. The study was conducted through observing the counseling services performed by the community pharmacists who participated in the study. Results: Two hundred and thirty-five forms were completed in eleven community pharmacies. A total of 44.4% of the counseling skills was found to be performed adequately, while only 20.1% of the counseling contents were performed adequately. Conclusions: The overall standard of medication counseling services provided to patients to improve usage of their medications, and consequently, their well-being was poor.